Validity And Practicality of PBL-Based Student e-Worksheets in Improving Physics Problem-Solving Skills - Amanda Ramadhona; I Wayan Distrik; Fatkhur Rohman (Department of Physics Education, Universitas Mataram, 2026)
Problem-solving skills are an important factor in physics learning. Efforts to improve problem-solving skills in physics require PBL-based electronic worksheets. This study aims to develop a valid and practical PBL-based electronic worksheet to improve physics problem-solving skills in the context of global warming. This type of research is development research that follows the research model developed by Thiagarajan, which consists of 4 stages: define, design, development, and dissemination. The PBL-based electronic worksheets development method to improve problem-solving skills in this research and development consists of 3 stages: the define stage, used to analyze student and teacher needs for PBL-based electronic worksheets; curriculum analysis; data analysis of student skills in solving physics problems; and searching for articles related to problem-solving skills. At this stage, data on students’ problem-solving skills and the importance of electronic worksheets in physics learning are collected. The design stage is used to create the electronic worksheets’ design. At this stage, a problem-based electronic worksheet design is produced. The development stage involved validity tests conducted by 3 experts: 2 physics education lecturers and 1 physics teacher. At this stage, a valid PBL-based electronic worksheet was produced, as indicated by an average content validity of 4.31 and construct validity of 4.32, categorized as valid. The next test was the practicality of the PBL-based electronic worksheets. The practicality test was conducted by implementing the electronic worksheets with students studying global warming. This stage resulted in practical electronic worksheets, as indicated by an average implementation rate of 86% and Positive student responses (77%) stating that electronic worksheets were easy to understand. In comparison, 23% of students said electronic worksheets were a bit difficult to understand. This indicates that the PBL-based electronic worksheets are easy for teachers to implement and can be used by students in physics learning.